Angiotensin-Converting Enzyme (ACE) level, but not ACE gene polymorphism, is associated with prognosis of COVID-19 infection: Implications for diabetes and hypertension - HAKLAR, GONCAGÜL (My University, 2023)
Background The renin-angiotensin-aldosterone system was shown to be activated in severe COVID-19 infection. We aimed to investigate the relationship between angiotensin converting enzyme (ACE) levels, ACE gene polymorphism, type 2 diabetes (T2DM), and hypertension (HT) and the prognosis of COVID-19 infection. Methods This cross-sectional study analyzed the clinical features of adult patients with SARS-CoV-2 infection. ACE gene analysis and ACE level measurements were performed. The patients were grouped according to ACE gene polymorphism (DD, ID or II), disease severity (mild, moderate, or severe), and the use of dipeptidyl peptidase-4 enzyme inhibitor (DPP4i), ACE-inhibitor (ACEi) or angiotensin receptor blocker (ARB). Intensive care unit (ICU) admissions and mortality were also recorded. Results A total of 266 patients were enrolled. Gene analysis detected DD polymorphism in the ACE 1 gene in 32.7% (n = 87), ID in 51.5% (n = 137), and II in 15.8% (n = 42) of the patients. ACE gene polymorphisms were not associated with disease severity, ICU admission, or mortality. ACE levels were higher in patients who died (p = 0.004) or were admitted to the ICU (p37.092 ng/mL, AUC: 0.775, p<0.001). Conclusion Our findings suggest that higher ACE levels, but not ACE gene polymorphism, ACEi/ARB or DPP4i use, were associated with the prognosis of COVID-19 infection. The presence of HT and T2DM and ACEi/ARB or DPP4i use were not associated with mortality or ICU admission.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary